PENGARUH PERSONAL SELLING TERHADAP VOLUME PENJUALAN TANAMAN HIAS VITKA GARDENIA BATAM - Kurnia, Okki (JURNAL MANAJEMEN KULINER, 2022)
The purpose of this research is to determine the effect of personal selling on the Sales Volume at Gardenia VITKA Batam. The sample used in this study amounted to 30 customers  ,sampling technique, namely the sampling technique using the entire population as a sample.. Data analysis techniques used simple linear regressions analysis. The results showed a coefficient value (r) of 795, a coefficient of determination (r2) of 0.713, a significance value of 0.000 <0.05, t count value is 8.338 and t tabel is 1.808. The results of this research indicate that (1) with r value has a strong relationship between personal selling and the sales volume, (2) with r2 value means personal selling have an sales volume. attandent of 79.3%, (3) with significance value means the personal selling variable (X) effects the sales volume variable (Y), (4) from t count value thus H0 is rejected and H1 is accepted.